Fight like a girl : how to be a fearless feminist - Seely, Megan (New York University Press, 2019)
"A blueprint for the next generation of feminist activists. Fight Like a Girl offers a vision of the past, present, and future of feminism. With an eye toward what it takes to create actual change and a deep understanding of women's history and the key issues facing girls and young women today, Megan Seely offers a pragmatic introduction to feminism. Written in an upbeat and personal style, Fight Like a Girl offers an overview of feminism, including historical roots, myths and meanings, triumphs and shortcomings. Sharing personal stories from her own experience as a young activist, as a mother, and as a teacher, Seely offers a practical guide to getting involved, taking action, and waging successful events and campaigns. The second edition addresses more themes and topics than before, including gender and sexuality, self-esteem, reproductive health, sexual violence, body image and acceptance, motherhood and family, and intersections of identities, such as race, gender, class, and sexualities. Fight Like a Girl is an invaluable introduction to both feminism and activism, defining the core tenets of feminism, the key challenges both within and outside the feminist movement, and the steps we can take to create a more socially just world."--